Nyeruan: Traditional Medicine of the Sasak Tribe in the Perspective of Islam, Medicine and Legislation in Indonesia - Lenny Herlina; Arfi Syamsun; Ida Lestari Harahap; Pujiarohman Pujiarohman (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to understand the history of the emergence of the traditional nyeruan healing tradition, how the treatment procession is carried out, how this treatment is in the view of Islam and modern health science. This research lasted for six months using qualitative methods with a phenomenological approach. Determining informants in this study used snowball sampling. The data collection techniques use participant-observation techniques, interviews, documentation, and also triangulation. Data analysis in this research uses the Social Construction theory of Peter L. Berger and Tomas Luckman, and Herbert Blumer's Symbolic Intractionism theory. Based on the research results, it shows that the traditional healing tradition of nyeruan does not violate the laws and regulations in Indonesia, so the practice is still being preserved, especially among the Sasak community